THE SIGNIFICANCE OF PROFESSIONAL-GNOSTIC PREPARING OF THE FUTURE FOREIGN LANGUAGE INSTRUCTOR - Hamdamov Erkin Ergashevich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
The article gives data on competence, which is one of the foremost genuine issues in pedagogics nowadays. Suppositions on the proficient and gnostic competence of a future English teacher was analyzed and proposals were created.